Future of the IT Industry Post-Covid - Mr. Vineet Kapshikar (Pune Corporate Citizen, 2021)
What will Covid-19's legacy be? Crisis can be a catalyst or can speed up changes that are on the way-it almost can serve as an accelerant. To deliberate on important aspects that are reshaping the IT Industry, Mahratta Chamber of Commerce, Industries and Agriculture organised a session on Future of IT Industry Post-Covid and Key Learnings of the Past Fifteen Months.
Keywords: Information Technology